2019
DOI: 10.1088/1755-1315/316/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

Methodical approach to increase efficiency of use of wood resource potential of the region

Abstract: The article deals with the problems of increasing the efficiency of wood resources processing. It shows the developed methodical approach to increase the processing efficiency. It consists of five stages, which all are disclosed in detail providing examples. Approbation of the proposed approach justifies the expediency of its use and substantial economic benefits for wood processing enterprises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…при этом виды, типы и марки приобретаемых машин могут быть различными, так как рельеф местности, почвенно-грунтовые условия, средние запас древостоя, запас на 1 га и т. д. у разных лесхозов неодинаковые. кроме того, эффективность работы как лесозаготовительных предприятий, так и лесной отрасли в целом во многом определяется существующей дорожной сетью и возможностями ее совершенствования [19][20][21][22][23][24][25][26].…”
Section: объекты и методы исследованияunclassified
“…при этом виды, типы и марки приобретаемых машин могут быть различными, так как рельеф местности, почвенно-грунтовые условия, средние запас древостоя, запас на 1 га и т. д. у разных лесхозов неодинаковые. кроме того, эффективность работы как лесозаготовительных предприятий, так и лесной отрасли в целом во многом определяется существующей дорожной сетью и возможностями ее совершенствования [19][20][21][22][23][24][25][26].…”
Section: объекты и методы исследованияunclassified
“…Wood processing, as a follow-up industry to forest harvesting and transportation, is a key step in enhancing the synthetic utilization rate of wood in the forestry sector [1,2]. Compared to other industrial fields, the wood processing industry has a relatively late startup and slow development, and with the increasing demand for wood products, advanced processing machinery, such as multi-axis CNC, industrial robots, and manipulators, are urgently needed to improve mechanization and automation levels in wood processing [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have investigated the efficiency of wood-processing enterprises. Medvedev et al [3] analysed wood-processing enterprises and revealed the role of the optimal use of wood resources for enhancing their efficiency. In similar research, Lähtinen [4] outlined that diversified tangible and intangible resources are the key tools for the improvement of the economic performance of wood-processing enterprises.…”
Section: Introductionmentioning
confidence: 99%